Lebanese Pharmacists’ Knowledge and Attitude toward Cannabis Medical Use Legality - Lynne H. Jaffal; Nathalie Lahoud; Salam Zein; Sanaa Awada; Dalia Khachman (Dr. Sulaiman Al Habib Medical Journal, 2020)
Medical cannabis legalization in Lebanon has been a controversial issue. No research has been done to study the aspects of knowledge and attitudes toward its prescription in Lebanon. The primary objective of this study was to assess the level of knowledge and attitude of Lebanese community pharmacists toward its legalization. The secondary objective focused on identifying the predictors of their corresponding knowledge and attitude. A cross-sectional survey was conducted using a sample of 233 Lebanese community pharmacists. A questionnaire comprising questions about sociodemographic details, knowledge, attitude, and preferences for getting information concerning medicinal cannabis was used for data collection over a period of 3 months. Four knowledge-related scores were computed, and descriptive, bivariate, and multivariate analysis was performed using SPSS version 23 (SPSS Inc., Chicago, IL, USA). About 51% of pharmacists were considered to have a good level of knowledge. More than half of the community pharmacists had good knowledge about its uses, side effects, and interactions. Although only 44.7% supported cannabis legalization in Lebanon, 79.4% agreed that it should be present in prescriptions for certain indications. Moreover, associations were found between knowledge and experience, source of information, residence, and hours spent in pharmacy. Furthermore, attitude toward cannabis prescription is associated with residence, degree perceived, having patients that can benefit, and comfort to explain cannabis efficacy. Effective educational strategies should be implemented in Lebanon in order to improve knowledge regarding cannabis not only among pharmacists but the community as a whole, and thus aid in its proper use for therapeutic purposes rather than recreational uses.